Interactive effects of chronic anthropogenic disturbances on Prosopis woodland structure in the Central Monte, Argentina - Szymañski, Carolina (2022)
In drylands all over the world, chronic anthropic disturbances are relevant factors for woodland degradation. Different disturbances can potentially interact to change vegetation structure. Knowing woodland structure is crucial for better predicting forest dynamic because trees of different sizes significantly affect the regeneration processes, number of saplings and young trees, crown traits and competition attributes. Throughout the Monte biogeographic region, grazing and wood extraction are the main anthropogenic disturbances on Prosopis dry woodlands that can generate modifications in key ecosystem processes. First, we aimed to assess woodland structure at sites under chronic anthropic disturbances. Subsequently, we explored how the combination of grazing and wood extraction affected the population structure of P. flexuosa considered by classes: Seedlings, saplings and adults. We found that sites under disturbances presented a high density of trees of smaller sizes. Besides, the interaction effect between grazing and wood extraction depended on the intensities of each of the disturbances. The combination of high intensities of both grazing and wood extraction negatively affected the abundance of all classes, but low or moderate grazing intensities combined with high wood extraction had a positive effect on the abundance of saplings and adults. High intensities of co-occurring disturbances decreased seedling abundance affecting forest recruitment which also was negatively reflected in sapling and adult abundance. However, the combination of low or moderate grazing and high wood extraction generated a woodland structure characterized by few seedlings, and many saplings and adult trees of small size. Application of management options (e.g., spatial or temporal separation of human use, programmed management of grazing and wood extraction intensities or planned practices as wood removal for local use) should contribute to enhance the provision of ecosystem services in Prosopis sp. woodlands without risking regeneration persistence and improving the woodland structure.